Blogs literários, consumo de literatura e a formação da identidade de um leitor-protagonista - Carvalho, Dorama de Miranda (2018)
The purpose of this study is to present the formation of a reader-protagonist in the current Brazilian literary scene, based on the analysis of the discourses generated in blogs about literature and the intersection with other social networks, especially YouTube. The goal is to show that there are new ways of accessing reading and that bloggers and youtubers are representatives of various literary consumption practices. The course of research and the discursive analysis of 12 blogs indicated the emergence of subjects that are transforming the dynamics of the book sector, with reviews and commentaries in social networks, both on book launches and on classical works. The printed book is highlighted even in a scenario of sales retraction and allows the emergence of new actors in literary criticism. The work resulted in some points that deserve to be highlighted: the current reading scenario in Brazil; the reader in a universe of media consumption of literature; convergence of media platforms as a generator of new identity formations; the discourses aimed at specific audiences and, as a consequence, the rise of authors, genres and literary styles.